2021
DOI: 10.1021/acs.jpcc.1c01603
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Sum Frequency Spectroscopy Study of Alcohol Adsorption on Thin-Film TiO2 at Ambient Pressure and Temperature

Abstract: Surface-sensitive vibrational sum frequency spectroscopy (vSFS) has been utilized to study the adsorption chemistry of small alcohols, namely, methanol, ethanol, 1propanol, and 2-propanol on TiO 2 thin films under near-ambient conditions. The vSF spectra in the C−H region reveal that methanol and ethanol adsorb both molecularly and dissociatively, while 1-propanol and 2-propanol are solely detected in the molecular form. The different adsorption behavior suggests that the extent of dissociation decreases from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…By sum‐frequency spectroscopy, the adsorption of 2‐propanol on TiO 2 was detected to take place molecularly [8] . On a SrTiO 3 perovskite with a mainly exposed (100) facet, an orientation of the alcohol with the C−H group pointing to the surface was found.…”
Section: Introductionmentioning
confidence: 98%
“…By sum‐frequency spectroscopy, the adsorption of 2‐propanol on TiO 2 was detected to take place molecularly [8] . On a SrTiO 3 perovskite with a mainly exposed (100) facet, an orientation of the alcohol with the C−H group pointing to the surface was found.…”
Section: Introductionmentioning
confidence: 98%
“…The additional steric hindrance from two methyl groups perhaps alters the adsorption structure with O–H bond pointing to the O b nearby to other structures at high 2-propanol coverage. Moreover, a recent vibrational sum frequency spectroscopy study of alcohol adsorption on thin-film TiO 2 shows that the methyl groups are preferentially oriented with their symmetry axis pointing in a direction close to the surface normal for methanol, ethanol, and 1-propanol adsorption on TiO 2 . However, for 2-propanol, the methyl groups exhibit a larger tilt angle.…”
Section: Resultsmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ), as one of the most explored photocatalysts, has been widely applied in many areas, including the photodegradation of organic pollutants, solar cells, sensors, photocatalytic hydrogen production, and so on. Therefore, TiO 2 photocatalysis has attracted significant attention in recent years in both fundamental investigations and industry applications, especially in the area of photocatalytic degradation of organic pollutants [such as indoor air, volatile organic compounds (VOCs), pharmaceuticals, and personal care products in water]. Although TiO 2 photocatalysis has been widely used in these areas, a deep understanding in the fundamental processes that underlie the photocatalytic reactions in the applications with TiO 2 is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Sims et al used VSFG to study the growth of methoxysilane films and found that the presence of a physisorbed layer is important in the molecular self-assembly process . Hasselbrink and co-workers used VSFG to study the adsorption of different alcohol molecules onto TiO 2 surfaces . VSFG was used by Dramstad et al to examine the structure of pentacene thin films, and von Domaros et al used VSFG measurements in conjunction with molecular modeling to determine molecular orientation at squalene–air and squalene–oil interfaces .…”
Section: Hard Materials and Nanoparticlesmentioning
confidence: 99%
“…10 Hasselbrink and co-workers used VSFG to study the adsorption of different alcohol molecules onto TiO 2 surfaces. 11 VSFG was used by Dramstad et al to examine the structure of pentacene thin films, 12 and von Domaros et al used VSFG measurements in conjunction with molecular modeling to determine molecular orientation at squalene−air and squalene−oil interfaces. 13 The mechanism for atomic layer deposition of Pt using MeCpPtMe 3 and O 2 reactants was studied using VSFG by Kessels and co-workers.…”
Section: ■ Hard Materials and Nanoparticlesmentioning
confidence: 99%